A Study into Utilization Building Automation System (BAS) In Energy Efficiency of HVAC system at Government Hospital in Kuala Lumpur - NUR IZZAH BINTI SHAMSURI (Progress in Engineering Application and Technology, 2023)
A Building Automation System (BAS) is a centralized control system that monitors and manages multiple building systems like HVAC (Heating, Ventilation, and Air Conditioning), lighting, security, fire safety, and other mechanical and electrical systems. Building automation systems (BAS) aid in the optimization of building performance, energy efficiency, comfort, and overall operational effectiveness. BAS systems have evolved over the course of several decades. Building automation was initially accomplished using basic control systems that worked independently. HVAC control is one of the key roles of a BAS system. It allows temperature, humidity, and ventilation within a building to be controlled depending on occupancy, time schedules, and environmental factors. HVAC operations may be optimized using BAS systems to decrease energy usage while preserving occupant comfort. The rate of global population growth has increased the rate of energy demand over the last few decades. The focus of building energy management was on HVAC which contributed 50% of building energy consumption. Defective actuators, valves, and dampers are the primary source of the building automation system in energy efficiency of HVAC system. The objective of the study is to identify the types of Building Automation System (BAS) used in Pusat Perubatan Universiti Malaya (PPUM), to determine energy efficiency using BAS in HVAC energy performance at PPUM and to analyse energy usage from real BAS data. In this study, to determine the pattern on of the situation, quantitative and qualitative. The data collected were analysed using Microsoft Excel. A BAS system can reduce the energy consumption of an HVAC system by using advanced control strategies. Temperature, airflow, and ventilation may be monitored and adjusted based on occupancy, time of day, and other parameters. As a result, hospitals save energy, have lower operational expenses, and have a cleaner impact.